Otolith and Genomic Data Reveal Temporal Insights Into Stocking Across a Large River Basin in a Mobile, Long‐Lived Australian Freshwater Fish Species - Katherine A. Harrisson; Luciano B. Beheregaray; Christopher M. Bice; Emily J. Booth; Chris J. Brauer; Gavin L. Butler; David Dawson; Olga Dudchenko; Benjamin G. Fanson; Graeme Hackett; Annique Harris; Matthew J. Jones; et al. (Molecular Ecology, 2025)
Freshwater ecosystems and their biota are under increasing pressure from anthropogenic stressors. In response to declining fish stocks, hatchery and stocking programmes are widely implemented as core components of restoration and management strategies, with positive outcomes for some wild populations. Despite this, stocking remains contentious due to potential genetic and ecological risks to wild populations. Monitoring and evaluation of stocking outcomes are critical to ensuring the long‐term sustainability of wild populations, but identification of stocked individuals post‐release remains a key challenge, particularly for mobile species. In this study, we combined otolith (natal origin and age) and genomic data to identify stocked individuals and evaluate the genetic implications of stocking for a culturally and socioeconomically important and mobile freshwater fish, golden perch Macquaria ambigua (family: Percichthyidae), across Australia's Murray–Darling Basin (MDB). We also generated a chromosome‐level genome assembly. Many close kin were detected across the MDB, increasing in prevalence over recent decades and mostly of hatchery origin. Rivers with many close kin were associated with low effective population sizes ( N e

Rationale and design of the Dog Aging Project precision cohort: a multi-omic resource for longitudinal research in geroscience - Jena Prescott; Amber J. Keyser; Paul Litwin; Matthew D. Dunbar; Robyn McClelland; Audrey Ruple; Holley Ernst; Brianna L. Butler; Mandy Kauffman; Anne Avery; Benjamin R. Harrison; Maria Partida-Aguilar; et al. (GeroScience, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Cyclones and skinny dolphins: adaptation pathways for Pacific communities under rapid global change - Matthew J. Colloff; James R.A. Butler; Nat Burke; John Morley; Lorrae van Kerkhoff; Zelda Hilly; Richard B. Makini-Purcell; Jamal Namo; Remy Barua; Kathryn Michie; Minnie Rafe; Slade Ririmae (Climate and Development, 2024)

Gastric mill ossicles record chronological age in the Caribbean spiny lobster (Panulirus argus) - Emily Hutchinson; Thomas R. Matthews; Erica Ross; Samantha Hagedorn; Mark J. Butler (Fisheries Research, 2024)

Overcome imposter syndrome: Contribute to working groups and build strong networks - Amanda E. Bates; Megan A. Davies; Rick D. Stuart-Smith; Natali Lazzari; Jonathan S. Lefcheck; Scott D. Ling; Camille Mellin; David Mouillot; Anthony T.F. Bernard; Scott Bennett; Christopher J. Brown; Michael T. Burrows; et al. (Biological Conservation, 2024)

Environmental Effects on the Seasonal Distribution of an Estuarine Species Neoarius graeffei in Northern New South Wales, Australia - Lauren J. Stoot; Gavin L. Butler; Yuri Niella; Gregory S. Doran; Jason D. Thiem; Matthew D. Taylor; Lee J. Baumgartner (Estuaries and Coasts, 2024)
Coastal river systems provide essential habitats for a diversity of fish species that transition marine, estuarine, and freshwater environments to complete their lifecycles. Movement among and within these environments is important to access resources that optimise growth, survival, and reproduction. Knowledge on the movements, including the drivers, underpins management strategies, although this information is often lacking for many species. We used acoustic telemetry to quantify the relative importance of a range of abiotic stimuli in relation to seasonal movement patterns in blue salmon catfish Neoarius graeffei throughout an unregulated coastal river catchment, the Clarence River in northern New South Wales, Australia. Neoarius graeffei continuously occupied the Clarence River system for the duration of the 1-year study and were mostly confined to estuarine reaches, with occasional movement into freshwater habitats. Seasonal differences in habitat occupation were observed, with N. graeffei using habitats close to the river mouth in winter and upstream estuary habitats in spring. Broad-scale movement patterns were influenced by both water temperature and river flow, and high-flow events (> 1.5 m) resulted in short-term changes (~ 10 days) in habitat use. Sex-specific differences in seasonal habitat use were also observed which we hypothesise is linked to contrasting energetic investment in reproduction. The response of N. graeffei to changes in river flow highlights the need for assessment on these impacts for estuarine-dependent species more broadly, in the face of climate change and increased river regulation.

Forecasting suitable areas for wind turbine occurrence to proactively improve wildlife conservation - Matthew A. Boggie; Matthew J. Butler; Steven E. Sesnie; Brian A. Millsap; David R. Stewart; Grant M. Harris; James C. Broska (Journal for Nature Conservation, 2023)

In vivo dissection of Rhoa function in vascular development using zebrafish - Laura M. Pillay; Joseph J. Yano; Andrew E. Davis; Matthew G. Butler; Megan O. Ezeude; Jong S. Park; Keith A. Barnes; Vanessa L. Reyes; Daniel Castranova; Aniket V. Gore; Matthew R. Swift; James R. Iben; et al. (Angiogenesis, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

Development of a quantitative PCR method for screening ichthyoplankton samples for bigheaded carps - Andrea K. Fritts; Brent C. Knights; James H. Larson; Jon J. Amberg; Christopher M. Merkes; Tariq Tajjioui; Steven E. Butler; Matthew J. Diana; David H. Wahl; Michael J. Weber; John D. Waters (Biological Invasions, 2019)

Does fish herding enhance catch rates and detection of invasive bigheaded carp? - Steven E. Butler; Anthony P. Porreca; Scott F. Collins; Jonathan A. Freedman; Joseph J. Parkos; Matthew J. Diana; David H. Wahl (Biological Invasions, 2019)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

A temperate palaeodiversity peak in Mesozoic dinosaurs and evidence for Late Cretaceous geographical partitioning - Philip D. Mannion; Roger B. J. Benson; Paul Upchurch; Richard J. Butler; Matthew T. Carrano; Paul M. Barrett (Global Ecology and Biogeography, 2012)
Aim Modern biodiversity peaks in the tropics and declines poleward, a pattern that is potentially driven by climate. Although this latitudinal biodiversity gradient (LBG) also characterizes the marine invertebrate fossil record, distributions of ancient terrestrial faunas are poorly understood. This study utilizes data on the dinosaur fossil record to examine spatial patterns in terrestrial biodiversity throughout the Mesozoic. Location We compiled data on fossil occurrences across the globe. Methods We compiled a comprehensive dataset of Mesozoic dinosaur genera (738), including birds. Following the utilization of sampling standardization techniques to mediate for the uneven sampling of the fossil record, we constructed latitudinal patterns of biodiversity from this dataset. Results The dominant group of Mesozoic terrestrial vertebrates did not conform to the modern LBG. Instead, dinosaur diversity was highest at temperate palaeolatitudes throughout the 160 million year span of dinosaurian evolutionary history. Latitudinal diversity correlates strongly with the distribution of land area. Late Cretaceous sauropods and ornithischians exhibit disparate LBGs. Main conclusions The continuity of the palaeotemperate peak in dinosaur diversity indicates a diminished role for climate on the Mesozoic LBG; instead, dinosaur diversity may have been driven by the amount of land area among latitudinal belts. There is no evidence that the tropics acted as a cradle for dinosaur diversity. Geographical partitioning among major clades of herbivorous dinosaurs in the Late Cretaceous may result from the advanced stages of continental fragmentation and/or differing responses to increasing latitudinal climatic zonation. Our results suggest that the modern‐day LBG on land was only established 30 million years ago, following a significant post‐Eocene recalibration, potentially related to increased seasonality.

Consulting Forestry / Certification and Ecosystem Services - James Coufal; Carl Wiedemann; Jacob Gorman; Larry Teeter; Yaoqi Zhang; Michael Kilgore; Kristell Miller; Stephanie Snyder; Sun Chang; Miriam Davis; Stanley Asah; J. Mark Fly; et al. (Journal of Forestry, 2011)
45The industrialization of the United States throughout the 19th century resulted in the exploitation of millions of acres of timberland across the country. Logging during that era was described by critics as “cut out and get out” because the land was usually abandoned after the merchantable timber was exhausted. Concern about future timber supplies and the effect of logging on watersheds spurred the development of professional forestry after the Civil War. The first forestry leaders, including Bernhard Fernow and Gifford Pinchot, encouraged private non-industrial forest owners to sustainably manage their woodlands and specifically warned against destructive logging practices—including “cutting the best and leaving the rest”—aka high-grading. During the 1920s and 30s both the Forest Service and SAF spurred initiatives to encourage sustainable timber harvesting practices on private forestland. Although great progress has been made in forest management, logging on most private non-industrial forest land in the east has not changed significantly since the 19th century. Landowners usually sell timber without using the services of a forester, allowing the buyer to selectively cut the most valuable trees in the woodlot. Although this can reduce future value by 70-90%, it remains common practice because both the landowner and the timber buyer maximize short term income. The timber value and productivity of millions of acres of woodland throughout the United States have been significantly degraded as a result. This paper will trace the history of high-grading as described by forestry leaders from the 19th century through the 21st and will show that much work remains unfinished.

Wild Turkey (Meleagris gallopavo) association to roads: implications for distance sampling - Devin R. Erxleben; Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Markus J. Peterson; Nova J. Silvy; William P. Kuvlesky; David G. Hewitt; Stephen J. DeMaso; Jason B. Hardin; Megan K. Dominguez-Brazil (European Journal of Wildlife Research, 2011)

How many color metrics do we need? Evaluating how different color-scoring procedures explain carotenoid pigment content in avian bare-part and plumage ornaments - Michael W. Butler; Matthew B. Toomey; Kevin J. McGraw (Behavioral Ecology and Sociobiology, 2011)

A novel method for quantifying the glossiness of animals - Matthew B. Toomey; Michael W. Butler; Melissa G. Meadows; Lisa A. Taylor; H. Bobby Fokidis; Kevin J. McGraw (Behavioral Ecology and Sociobiology, 2010)

Relationships of red-cockaded woodpecker reproduction and foraging habitat characteristics in Arkansas and Louisiana - Matthew J. Butler; Philip A. Tappe (European Journal of Wildlife Research, 2008)

Wild turkey (Meleagris gallopavo) detectability from helicopters and ramifications for estimating abundance - Matthew J. Butler; Warren B. Ballard; Mark C. Wallace; Stephen J. DeMaso (European Journal of Wildlife Research, 2008)

The N-terminus of Himar1 mariner transposase mediates multiple activities during transposition - Matthew G. Butler; Sangita A. Chakraborty; David J. Lampe (Genetica, 2006)

Exogenous manganous ion at millimolar levels rescues all known dioxygen-sensitive phenotypes of yeast lacking CuZnSOD - Raylene J. Sanchez; Chandra Srinivasan; William H. Munroe; Matthew Alan Wallace; Jacob Martins; Tina Y. Kao; Kate Le; Edith Butler Gralla; Joan Selverstone Valentine (JBIC Journal of Biological Inorganic Chemistry, 2005)

Temporal patterns and transport processes in recruitment of spiny lobster ( Panulirus argus ) postlarvae to south Florida - C. A. Acosta; T. R. Matthews; M. J. Butler IV. (Marine Biology, 1997)